1997
DOI: 10.1126/science.275.5300.674
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Channel Regulation by Channel-Associated Protein Tyrosine Kinase Src

Abstract: The N-methyl-D-aspartate (NMDA) receptor mediates synaptic transmission and plasticity in the central nervous system (CNS) and is regulated by tyrosine phosphorylation. In membrane patches excised from mammalian central neurons, the endogenous tyrosine kinase Src was shown to regulate the activity of NMDA channels. The action of Src required a sequence [Src(40-58)] within the noncatalytic, unique domain of Src. In addition, Src coprecipitated with NMDA receptor proteins. Finally, endogenous Src regulated the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
475
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(502 citation statements)
references
References 28 publications
24
475
1
2
Order By: Relevance
“…Collectively, our results have unequivocally shown that increased tyrosine phosphorylation by Src accounts for the increased EPSC NMDA . Because tyrosine phosphorylation increases NMDAR currents and leads to LTP (Wang and Salter, 1994;Yu et al, 1997;Lu et al, 1998), the increased NMDAR activity may be the physiological basis for reelin-enhanced synaptic plasticity, such as elevated magnitude of pairing-induced LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our results have unequivocally shown that increased tyrosine phosphorylation by Src accounts for the increased EPSC NMDA . Because tyrosine phosphorylation increases NMDAR currents and leads to LTP (Wang and Salter, 1994;Yu et al, 1997;Lu et al, 1998), the increased NMDAR activity may be the physiological basis for reelin-enhanced synaptic plasticity, such as elevated magnitude of pairing-induced LTP.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may just add to an ever growing list of molecules that Src is able to phosphorylate. For example, it is clear that a number of receptors and channels can be phosphorylated by Src family members and that this phosphorylation can lead to altered activity (Holmes et al, 1996;Yu et al, 1997). The role and importance of phosphorylation by Src will need to be determined in each individual pathway.…”
Section: Kinase Domainmentioning
confidence: 99%
“…It has been assumed that this domain may be required for speci®c interactions between particular Src family kinases and downstream targets. Recent studies of Src's interaction with and phosphorylation of the NMDA receptor support this view ± phosphorylation is dependent on the Src unique region (Yu et al, 1997). Activation of Src during M phase is accompanied by phosphorylation of Src on certain Ser and Thr residues within the unique domain ± mutation of these residues can lower activation of Src during M phase, but does not eliminate it (Shalloway et al, 1992).…”
Section: Function Of the Unique Domainmentioning
confidence: 99%
“…Average mEPSCs observed in the first two min after breaking in whole-cell configuration were used as control and compared to averages obtained after 8-14 min in whole-cell. The AMPA component was measured at the maximum amplitude during the first 5 ms in each event and the NMDA component as the integrated charge between 5-150 ms after the peak value 15 . Mean mEPSCs contained at least 30 traces.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…However, pharmacological blockade of these receptors in humans is deleterious because the activity of NMDARs is essential for many important physiological functions including breathing and locomotion 9,12,13 . A crucial signaling event for NMDAR-dependent neuroplasticity, including pain hypersensitivity 1,14 , is upregulation of NMDAR currents by mechanisms including relieving Mg 2+ blockade and receptor phosphorylation 15,16 . Thus, preferentially inhibiting mechanisms which upregulate NMDARs without affecting basal channel activity represents a strategy that may suppress pain hypersensitivity without impairing key physiological functions.…”
mentioning
confidence: 99%